A review on the operating conditions of producing bio‐oil from hydrothermal liquefaction of biomass. (21st January 2016) - Xue, Yuan; Chen, Hongyan; Zhao, Weina; Yang, Chao; Ma, Peng; Han, Sheng
Summary: Hydrothermal liquefaction (HTL) is a promising technology that involves converting biomass into a liquid energy carrier called bio‐oil in sub/supercritical water. The unique physico‐chemical properties of bio‐oil, particularly its remarkably high energy density, renewability, and sustainability, can address current global environmental challenges and energy crisis. This review assesses the influence of operating parameters, including biomass type, reaction temperature, holding time, biomass/H2 O ratio, heating rate, pressure, and atmosphere, and catalysis, on the yield and quality of bio‐oil. The existing problems in HTL are also analyzed, and its further development is explored. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : As shown in Figure 1, hydrothermal liquefaction produces liquid bio‐oil in the presence of H2 O and a suitable catalyst at a moderate‐to‐high temperature (200–500 °C) and pressure (5–30 MPa). A liquid bio‐oil is obtained as the main product, with gaseous‐phase, aqueous‐phase, and solid‐phase by‐products, and almost all products can be utilized. However, the hydrothermal liquefaction of biomass was influenced by many parameters, such as biomass type, holding time, biomass/H2 O ratio, reaction temperature, heating rate, pressure, and atmosphere, and catalysis.